associate professor - Marijana Markovikj; Eleonora Serafimovska (The Faculty of Law, Goce Delchev University in Shtip, Republic of Macedonia, 2019)
On 17 June 2018, the Republic of Macedonia and the Republic of Greece signed the Prespa Agreement that closed the long-standing dispute about the name of the Republic of Macedonia. The government then decided to hold a consultative referendum, and the campaign, although unofficial, has already begun. By September 30th, when the referendum was scheduled in the media, numerous personalities appeared: journalists, professors, writers, civil activists, experts from various fields, as well as holders of political functions in the role of columnists, called by the media to say their opinion and position on the change of the constitutional name of their country. The survey is an attempt to see who people were signed on the texts entitled as columns in the period from the signing of the Prespa Agreement to the day of the referendum vote in electronic versions of newspapers, as well as internet portals /information websites; from which sphere of professional life they come; by which dynamic their texts appear; and with which discourse of emotion they try to influence the opinion of the audience. The analysis showed that readers of internet portals witnessed a large number of expert opinions in the research period, and most of them were with negative emotional charge, so there is a dilemma about the loss of the value of the column and its potential positive benefits in making such important decisions for a nation, such as the change of the state name.
ДИСКУРС НА ЕМОЦИИ ВО КОЛУМНИТЕ ВО ИНТЕРНЕТ - МЕДИУМИТЕ ВО ПЕРИОДОТ ПРЕД РЕФЕРЕНДУМОТ ЗА ПРОМЕНА НА УСТАВНОТО ИМЕ НА РЕПУБЛИКА МАКЕДОНИЈА
Keywords: Discourse of Emotions, Referendum, Internet Media, Columnists, Prespa Agreement